Keterkaitan Senam Yoga dengan Pengurangan Dismenore Primer pada Remaja Putri: The Relationship Between Yoga and the Reduction of Primary Dysmenorrhea in Adolescent Girls - Jilan Fadhilah; Desi Hidayanti; Saur Sariaty; Lola Noviani Fadhilah (Journal of Health, 2026)
Background: Dysmenorrhea disrupts the social, academic, and physical and psychological activities of adolescent girls. Globally, more than 50% of women experience dysmenorrhea, with a prevalence of 72% in Sweden and nearly 90% in the United States. In Indonesia, the prevalence of dysmenorrhea reaches 64.25%, with 54.89% of them experiencing primary dysmenorrhea, especially among adolescent girls aged 14-19 years. In West Java, 54.9% of women experience dysmenorrhea. Yoga is believed to reduce the severity of dysmenorrhea, as it helps reduce menstrual pain and fluid buildup in the lower back. Objective: This study aims to determine the effect of yoga exercises on primary dysmenorrhea in adolescent girls. Methods: This study used a quasi-experimental method with a one-group pretest-posttest design. The study was conducted from April to May 2024. The sample consisted of 30 respondents from SMPN 15 Kota Bandung. The Suryanamaskar yoga exercise series was performed four times over two weeks. Pain scale measurements were taken using the WalIDD score instrument, which was designed to integrate dysmenorrhea in relation to school activities or daily activities. Results: This study showed that the average pain scale before the intervention was 6.69 and the average after the intervention was 2.86. The Wilcoxon test results showed a P value of 0.00 < 0.005. These results indicate that yoga exercises can reduce primary dysmenorrhea in adolescent girls. Conclusion: Adolescents can reduce dysmenorrhea by practicing Suryanamaskar yoga exercises, while health workers can play an active role in promoting adolescent reproductive health through the implementation of yoga exercises, given their proven effectiveness in reducing dysmenorrhea pain.